Cost-Effectiveness Analysis of Pharmacotherapy for Hematemesis-Melena Treatment in Hospitalized Patients with Hepatic Cirrhosis - Doddy de Queljoe; Amelia Lorensia; Liana Widharta; Sugiarto Widjaja (The Indonesian Biomedical Journal, 2013)
BACKGROUND: Acute variceal haemorrhage is a complication of cirrhosis that can be life threatening. It is a pharmacist’s duty to ensure therapeutic and pharmaceutical care which is not only safe and effective for the patient but also is cost-effective in order to attain improvement of the patient’s quality of life. Therefore, pharmacoeconomic evaluation especially cost-effectiveness analysis (CEA), which compares costs and consequences of drug therapy, is needed. This study was aimed to evaluate the therapeutic cost-effectiveness of hematemesis-melena treatment in hepatic cirrhotic patients.METHODS: A total of 42 patients receiving vitamin K and vitamin K-transamin were studied retrospectively from patients’ medical records in 2 years and analyzed with cost-effectiveness grid and average cost-effectiveness ratio (ACER) based on Child-Turcotte-Pugh (CTP) Score.RESULTS: Cost-effectiveness grid was dominant for vitamin K in patients with CTP Score A. ACER analysis showed a lower score for vitamin K in all patients included CTP Score classification. There was no significant difference in duration of cessation of bleeding treatment in patients with vitamin K compared with vitamin K-transamin in patients with CTP Score A and B, while significant difference was found in patients with CTP Score C.CONCLUSION: Vitamin K appeared to be more cost effective as compared with vitamin K-transamin in all patients. The use of vitamin K had greater benefit than the combination with transamin in all patients and CTP Score classification, and thus should be considered as a primary therapy. Therefore, transamin addition as an alternative therapy for hepatic cirrhosis patients with hematemesis-melena should be considered.KEYWORDS: CEA, cost-effectiveness analysis, child-turcotte-pugh score, hepatic cirrhosis, hematemesismelena, vitamin K, transamin